Small remedies - Deshpande, Shashi (Viking, 2000)
The narrator of the novel is Madhu, Leela's niece who travels to Bhavanipur, Savithribai's home in her last years, to write a biography of Bai. Even as a child Madhu hadbeen intrigued by Bai's relationship with Ghulaam sab and with munni, their doughter. Now grieving the loss of her only son Aditya, Madhu tries to make sense of the lives of these three people, and in doing so, hopes to find a way out of her own despair. As the story unfolds, she goes back and forth in time, drawing out, remembering, and retelling the stories of Leela, Bai and Munni. And always in the foreground is Madhu's own story- of a life transformed in one traumatic moment that took away every thing she had loved and believed in: her marriage, her son and, very nearly, her sanity